Сommunicative activity of engineers-pedagogues in the process of vocational training at vocational technical educational institutions - Mefanik, M. (Problems of Engineer-Pedagogical Education, 2018)
This article describes some aspects of the educational activity of future engineers-pedagogues. It defines the essence of the communicative activities of engineers-pedagogues in the process of teaching students in vocational technical educational institutions. Special attention is focused on types and functions of their communicative activities, such as methodological, didactic, design, research, organizational, production and technological, diagnostic and communication ones. The communicative activity of engineers-pedagogues consists in performing actions aimed at engaging students in various activities and includes team-building and organization of group activities. The use of communication technologies allows organizing various types of individual and group profession-oriented activities of students. Communicative activities are aimed at establishing pedagogically appropriate relationship of the teacher with his or her students, their parents, other teachers and members of the public. Communication technologies make possible for an engineer-pedagogue to use different means of communication to keep in touch with students and their parents as well as with colleagues. The article highlights some peculiarities of professional training of students at vocational educational institutions as well as some features of relevant communicative activities.